(untitled) (Swiss Medical Weekly, 2014)
QUESTIONS UNDER STUDY: We sought to identify reasons for late human immunodeficiency virus (HIV) testing or late presentation for care. METHODS: A structured chart review was performed to obtain data on test- and health-seeking behaviour of patients presenting late with CD4 cell counts below 350 cells/µl or with acquired immunodeficiency syndrome (AIDS), at the Zurich centre of the Swiss HIV Cohort Study between January 2009 and December 2011. Logistic regression analyses were used to compare demographic characteristics of persons presenting late with not late presenters. RESULTS: Of 281 patients, 45% presented late, 48% were chronically HIV-infected non-late presenters, and an additional 7% fulfilled the <350 CD4 cells/µl criterion for late presentation but a chart review revealed that lymphopenia was caused by acute HIV infection. Among the late presenters, 60% were first tested HIV positive in a private practice. More than half of the tests (60%) were suggested by a physician, only 7% following a specific risk situation. The majority (88%) of patients entered medical care within 1 month of testing HIV positive. Risk factors for late presentation were older age (odds ratio [OR] for ≥50 vs <30 years: 3.16, p = 0.017), Asian versus Caucasian ethnicity (OR 3.5, p = 0.021). Compared with men who have sex with men (MSM) without stable partnership, MSM in a stable partnership appeared less likely to present late (OR 0.50, p = 0.034), whereas heterosexual men in a stable partnership had a 2.72–fold increased odds to present late (p = 0.049). CONCLUSIONS: The frequency of late testing could be reduced by promoting awareness, particularly among older individuals and heterosexual men in stable partnerships.